Response to Infliximab in Crohn’s Disease: Genetic Analysis Supporting Expression Profile - Luz María Medrano; Carlos Taxonera; Cristina González-Artacho; Virginia Pascual; María Gómez-García; Manuel Barreiro-de Acosta; José L. Pérez-Calle; Fernando Bermejo; Antonio López-Sanromán; Dolores Martín Arranz; Javier P. Gisbert; Juan Luis Mendoza; et al. (Mediators of Inflammation)
Substantial proportion of Crohn’s disease (CD) patients shows no response or a limited response to treatment with infliximab (IFX) and to identify biomarkers of response would be of great clinical and economic benefit. The expression profile of five genes (S100A8-S100A9, G0S2, TNFAIP6, and IL11) reportedly predicted response to IFX and we aimed at investigating their etiologic role through genetic association analysis. Patients with active CD (350) who received at least three induction doses of IFX were included and classified according to IFX response. A tagging strategy was used to select genetic polymorphisms that cover the variability present in the chromosomal regions encoding the identified genes with altered expression. Following genotyping, differences between responders and nonresponders to IFX were observed in haplotypes of the studied regions: S100A8-S100A9 (rs11205276*G/rs3014866*C/rs724781*C/rs3006488*A; P=0.05); G0S2 (rs4844486*A/rs1473683*T; P=0.15); TNFAIP6 (rs11677200*C/rs2342910*A/rs3755480*G/rs10432475*A; P=0.10); and IL11 (rs1126760*C/rs1042506*G; P=0.07). These differences were amplified in patients with colonic and ileocolonic location for all but the TNFAIP6 haplotype, which evidenced significant difference in ileal CD patients. Our results support the role of the reported expression signature as predictive of anti-TNF outcome in CD patients and suggest an etiological role of those top-five genes in the IFX response pathway.